2019
DOI: 10.1021/acs.jafc.9b02495
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Peptide from β-Casein That Enhances Spatial and Object Recognition Memory in Mice

Abstract: An increase in the aging population has spurred recent efforts to identify diet and lifestyle changes that help prevent cognitive decline. Several epidemiological investigations and clinical studies have indicated that consuming fermented dairy products prevents cognitive decline. Some peptides from whey including β-lactolin improve memory impairment; the intake of Camembert cheese has been shown to prevent Alzheimer’s in mouse models. To elucidate the molecular mechanisms underlying these preventive effects, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Meanwhile, the control, positive, and memory impairment model groups were administered equal volumes of 0.9% normal saline. At 6 weeks, all of the groups were injected with scopolamine solution (1 mg/kg bw) to induce the amnesia mouse model except for the control group, , and the positive group was administered piracetam solution (400 mg/kg bw). The behavioral test was carried out 30 min later by the WMT-100 Morris water maze video analysis system (Chengdu Taimeng Software Co., Ltd., Chengdu, China).…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, the control, positive, and memory impairment model groups were administered equal volumes of 0.9% normal saline. At 6 weeks, all of the groups were injected with scopolamine solution (1 mg/kg bw) to induce the amnesia mouse model except for the control group, , and the positive group was administered piracetam solution (400 mg/kg bw). The behavioral test was carried out 30 min later by the WMT-100 Morris water maze video analysis system (Chengdu Taimeng Software Co., Ltd., Chengdu, China).…”
Section: Methodsmentioning
confidence: 99%
“…β-Lactoglobulin, a major protein of whey, is rich in WY sequences, and digestion of whey effectively releases β-lactolin, along with other peptide containing WY sequences. In addition, we recently identified another novel bioactive peptide from β-casein that enhances memory functions [6]. Milk proteins including whey and casein would be effective source of bioactive peptides.…”
Section: Discussionmentioning
confidence: 99%
“…In the process of identifying the ingredients responsible for our previous findings, we screened bioactive peptides from digested β-casein and found KEMPFPKYPVEP peptides, which improve memory function in mice [6]. We further determined the tryptophan–tyrosine (WY) sequence-containing peptides that were abundant in Camembert cheese, including a lacto-tetrapeptide of glycine–threonine–tryptophan–tyrosine (GTWY) and β-lactolin, from β-lactoglobulin in whey digestion, and found that administrating these peptides improved hippocampus-dependent memory functions in mice [7].…”
Section: Introductionmentioning
confidence: 99%
“…The test was based on Ano's method with slight modification. [ 54 ] The NORT assay consisted of training phase and testing phase. In training phase, two identical objects (A and A′, blocks) were fixed opposite each other at the end of a black acrylic box (40 cm × 30 cm × 20 cm).…”
Section: Methodsmentioning
confidence: 99%